Experimental analysis of heat transfer coefficient in counter flow shell and helical coil tube heat exchanger with hybrid nanofluids to enhance heat transfer rate using in food processing industries - et. al., D. Sarath Chandra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The impact of overall heat transfer coefficient and the pressure drop on performance of a counter flow helical tube heat exchanger with Cu-Ni-water hybrid nanofluid are computed. To evaluate heat transfer rate for a mix of base fluid with copper and nickel nanoparticles of volume concentrations 0.02,0.04 and 0.06 are added. To control the sedimentation of nanoparticles in the base fluid Ultrasonication followed by magnetic stirrer method is used. In this work experiments are conducted with to enhance heat transfer rate rather than stability of nanoparticles. Experiments are conducted for different concentrations and coil turns under laminar flow regime. The results are shown that 0.04 % vol of Cu-Ni/H2O with 12 turns is more predominate foe food processing applications due to its consistency in maintaining a constant temperature.